Proline Priming Enhances Seed Vigour and Biochemical Attributes of Rice (Oryza sativa L.) during Germination - Cloee Kher Yan Kong; Rattanak Sambath Lee; Kamariah Hasan; Clement Kiing Fook Wong; Chui Yao Teh (Tropical Life Sciences Research, 2024)
Seed vigour is a desirable trait especially for direct seeded rice (DSR) cultivation. Seeds with high vigour could improve seed germination, support seedlings in competing with weeds for water and nutrients, and improving seedling establishment throughout the early stages of crop growth. The success of DSR system which account for more 25% of world cultivation areas is highly dependent on the seed vigour and seedling establishment. Seed priming is a promising technique to improve seed vigour. Proline is an amino acid that has been well studied for its roles in plants under different environmental stress conditions. Nevertheless, the effect of proline as a seed priming agent in improving seed vigour in rice remain elusive. In this research, the effect of 24 h of proline priming at various concentrations (0 mM, 1 mM, 2 mM, 10 mM and 20 mM) on rice seed vigour, amylase activity, and total soluble sugar (TSS) content of a Malaysia indica rice variety, MR269 was investigated. Results showed that seeds primed with lower concentration of proline (0 mM, 1 mM and 2 mM) had better germination responses while priming at high concentrations (10 mM and 20 mM) reduced seed germination. Among the concentration tested, priming with 1 mM proline enhanced seed vigour with significantly higher germination percentage (GP), germination rate index (GRI) and seedling vigour index (SVI). In addition, proline primed seeds also exhibited increased amylase activity and TSS content as compared to unprimed seeds. However, priming seed with 20 mM proline was detrimental to the seed vigour and seedling growth whereby lower GP, GRI and SVI and higher mean germination time (MGT) were observed. In short, this study shows that proline could be a potential seed priming agent to improve seed vigour in rice.